2017
DOI: 10.1038/srep40615
|View full text |Cite
|
Sign up to set email alerts
|

A mucin-like peptide from Fasciola hepatica instructs dendritic cells with parasite specific Th1-polarizing activity

Abstract: Fasciolosis is a trematode zoonosis of interest in public health and cattle production. We report here the immunostimulatory effect of a 66 mer mucin-like peptide from Fasciola hepatica (Fhmuc), which synergizes with lipopolysaccharide (LPS) to promote dendritic cell (DC) maturation, endowing these cells with Th1-polarizing capacity. Exposure of DCs to Fhmuc in presence of LPS induced enhanced secretion of pro-inflammatory cytokines and expression of co-stimulatory molecules by DCs, promoting their T cell stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 40 publications
2
15
0
1
Order By: Relevance
“…It has been reported that in fixed sheep lymph nodes, MHC-II is expressed at high levels by interdigitating cells present in the paracortex, at lower levels by the B lymphocytes present in the follicles, and at a lower level in macrophages from the medullary sinuses [13], an expression pattern also observed in our study. In the present study, the reduced MHC-II+ DC found in HLNs at 9 and 18 dpi, compared to the number in the UC group, agrees with the significant decrease in MHC-II in the peritoneal leukocytes of sheep experimentally infected with F. hepatica at 9 dpi [54], with the reduced expression of MHC-II in DC from buffalos cultured in the presence of ESPs from F. gigantica [20], and with the low MHC-II expression in DC of mice cultured in the presence of mucin-like peptide [30,65] or in the presence of FhTeg from F. hepatica [18].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…It has been reported that in fixed sheep lymph nodes, MHC-II is expressed at high levels by interdigitating cells present in the paracortex, at lower levels by the B lymphocytes present in the follicles, and at a lower level in macrophages from the medullary sinuses [13], an expression pattern also observed in our study. In the present study, the reduced MHC-II+ DC found in HLNs at 9 and 18 dpi, compared to the number in the UC group, agrees with the significant decrease in MHC-II in the peritoneal leukocytes of sheep experimentally infected with F. hepatica at 9 dpi [54], with the reduced expression of MHC-II in DC from buffalos cultured in the presence of ESPs from F. gigantica [20], and with the low MHC-II expression in DC of mice cultured in the presence of mucin-like peptide [30,65] or in the presence of FhTeg from F. hepatica [18].…”
Section: Discussionsupporting
confidence: 76%
“…On the other hand, it has been shown that recombinant forms of FhCL1 and FhGST can partially activate DC [10]. Moreover, a mucin-like peptide from F. hepatica (Fhmuc) induces parasite-specific adaptive immunity with increased levels of IFN-γ and specific IgG antibodies [30]. In a recent study, it was also reported that the interactions of DC with F. hepatica cathepsin L3 (FhCL3) confer a unique expression pattern of the cytokines IFN-γ and IL-13, which may be protective in this parasitosis or in other helminth infections [31].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to other F. hepatica ES products discussed here, but similar to FhCL1 and FhGST-si ( 41 ), Fhmuc elicits pro-inflammatory properties, with increased LPS-induced TLR4 expression in DCs and polarization of the T cell response ( 59 ). This ability of F. hepatica to modulate the host immune response may have potential implications for vaccination strategies ( 59 ). As F. hepatica ES products contain significant levels of glycans, it is probable that native F. hepatica mucin-like peptides undergo glycosylation, which is not represented with the synthetic peptide.…”
Section: Fasciola Hepatica Excretory-secretory Productsmentioning
confidence: 80%
“…Analysis of the NEJ stage of F. hepatica infection led to the discovery of proteins with similarities to mucins ( 57 , 58 ). A synthetic mucin-derived peptide (Fhmuc) increased peritoneal CD11b + MHCII + cells in mice exposed to LPS ( 59 ). In contrast to other F. hepatica ES products discussed here, but similar to FhCL1 and FhGST-si ( 41 ), Fhmuc elicits pro-inflammatory properties, with increased LPS-induced TLR4 expression in DCs and polarization of the T cell response ( 59 ).…”
Section: Fasciola Hepatica Excretory-secretory Productsmentioning
confidence: 99%
See 1 more Smart Citation